Tourism management synergies in Sub-Saharan Africa - Simplice Asongu; Mushfiqur Rahman; Richard Adu-Gyamfi; Raufhon Salahodjaev (African Governance and Development Institute (AGDI), 2022)
The purpose of this study is to assess how some governance dynamics such as political stability and the rule of law modulate the incidence of some macroeconomic factors (i.e. domestic investment and trade openness) on tourism development. The focus of this study is on 47 countries in sub-Saharan Africa with data from 2002 to 2018, and the Generalized Method of Moments is employed as the empirical strategy. From the findings, synergy effects are apparent in the role of the rule of law in modulating domestic investment for tourism development in terms of tourism receipts. It follows that, for the sampled countries, promoting tourism development can be most effective if policies for enhancing domestic investment and promoting the rule of law are implemented simultaneously.
Keywords: O10; O40; Z3; Z32; 330; Tourism Management; Economic Growth; Sub-Saharan Africa